Land degradation in the West-Central Free State: human-induced or climate variability, the perceptions of Abrahamskraal–Boshof district farmers. Issue 3 (2nd September 2017) - Rabumbulu, M.; Badenhorst, M.
Abstract: Abrahamskraal–Boshof district is a farming area located in the dry semi-arid west-central part of South Africa's Free State Province. The semi-arid, continental climate only permits dryland commercial agriculture of maize, sunflowers and stock farming. Land degradation is a problem throughout the world, is particularly more problematic in the developing countries where large parts are already degraded. The role of climate variability and biophysical factors as causes of land degradation are often overlooked. With general circulation models predicting an increase in aridity, particularly for areas in the lower latitudes, droughts will play an increasingly larger role in the promotion of land degradation in South Africa. This pilot study explores the causes of land degradation in the West-Central Free State though the use of geographical data, climatological data-sets of the past 20 years and narratives from the local farmers. The paper looks at whether farmers perceive climate variability, biophysical factors or human activities as the primary cause of land degradation. Climatological data largely correlate with most of the farmer's perceptions of drought. Land degradation is present in all the farms where the farmers farm with Bonsmara cattle and sheep; they do not allow cattle and sheep to graze together in a paddock and keep a slightly higher stocking rate. Despite these findings, farmers largely lay the blame for the degradation on the geophysical environment of the area.